Tingkat Kepuasaan Pengguna Terhadap Aplikasi Mobile Banking Di Kalangan Mahasiswa Universitas Nias - Waruwu, Carolina Sayangi Cahaya; Waruwu, Henny Grace Enjel Naindelin (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This research aims to analyze the level of student satisfaction with the mobile banking application. Along with the rapid development of digital technology, mobile banking applications are increasingly in demand, especially by students who prioritize ease in financial transactions. This research was conducted on students at Nias University to find out the extent to which the mobile banking application meets their expectations and needs. Primary data was collected through questionnaires distributed to 300 students who actively used the mobile banking application. The research results show that the majority of students are satisfied with the ease of use and speed of transactions offered by the mobile banking application. However, several concerns were found regarding security features, indicating the need for improvements to the security aspects of the application.